lunes, 24 de octubre de 2011

Leyes de conjuntos

DE IDEMPOTENCIA
A∪
 
ASOCIATIVA
(
(
 
A∪
B = B∪ A     A∩ B = B∩ A
DISTRIBUTIVA

A ∪
(B∩  C) = (A∪B)∩  (A∪ C)
A ∩
DE IDENTIDAD
(B ∪C) = (A∩B)∪ (A∩C)
A∪
A ∪∅
DE INVOLUCIÓNA’)’ = A

DE COMPLEMENTO
A
∪A’ = U       A∩ A’ = ∅
U
’= ∅   ∅’= U
D’MORGAN
(
PRINCIPIO DE CONTEO
A∪B)’ = A’∩B’          (A ∩ B)’= A’∪B
n
(A∪ B) = n(A) + n(B) A∩ B =∅n(A ∪B) = n(A) + n(B) - n(A ∩B) A∩ B ≠  ∅
(
U = U A∩ U = A= A        A∩ ∅= ∅
 
CONMUTATIVA
A ∪B)∪ C = A∪ (B ∪C )A ∩B)∩ C = A ∩(B ∩C)
A = A        A∩A = A

No hay comentarios:

Publicar un comentario